1980
DOI: 10.1037/h0077668
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral methods for inferring anatomical linkage between rewarding brain stimulation sites.

Abstract: Rats lever pressed for concurrent electrical stimulation of the lateral hypothalamus and ventral tegmentum. The pulse-pair stimulation technique was used, with the first pulse of each pair applied to one electrode and the second to the other electrode; the intrapair interval was varied. The effectiveness of stimulation, measured behaviorally, increased abruptly (within .4 msec) as the intrapair interval was increased in the range from 1.0 to 2.0 msec These results, which do not resemble single-electrode refrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
109
2
2

Year Published

1980
1980
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(122 citation statements)
references
References 25 publications
9
109
2
2
Order By: Relevance
“…Not all of the results of the unilateral two-electrode experiment resemble those in Figure 7, Panel A. In fact, some curves look like those obtained from subjects with bilateral Shizgal et al, 1980, andYeomans, 1979. ) electrodes.…”
Section: Two-electrode Experimentsmentioning
confidence: 48%
See 2 more Smart Citations
“…Not all of the results of the unilateral two-electrode experiment resemble those in Figure 7, Panel A. In fact, some curves look like those obtained from subjects with bilateral Shizgal et al, 1980, andYeomans, 1979. ) electrodes.…”
Section: Two-electrode Experimentsmentioning
confidence: 48%
“…During the past decade, various long-axon, catecholaminergic components of the MFB have been suggested to serve this role. Shizgal et al (1980) reasoned that if such longaxon neurons were in fact the directly stimulated substrate for MFB self-stimulation, then it should be possible to demonstrate collision effects when two ipsilateral MFB self-stimulation sites were stimulated concurrently.…”
Section: Two-electrode Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…U sing the pulse-pair technique (Shizgal, Bielajew, Corbett, Skelton, & Yeomans, 1980), the manner in which the neurons mediating the aversive consequences of stimulation link these two sites is currently being investigated in our laboratory. Such data may choose between the possibilities outlined above.…”
Section: Morphine and Brain Stimulation 377 General Discussionmentioning
confidence: 99%
“…Thus, the search for the neural processes underlying positive reinforcement has most often focused on pathways traveling through the medial forebrain bundle. Studies of electrical brain self-stimulation have identified the medial forebrain bundle as a prime substrate for reward (Olds and Olds, 1965;Rolls, 1975;Wise and Bozarth, 1984), and the neurons directly stimulated by the electrode are apparently myelinated, fast-conducting, and descending neurons that have short refractory periods (Shizgal et al, 1980;Yeomans, 1989).…”
mentioning
confidence: 99%